Stakeholder´s analysis in e-learning software process development - Romero, Lucila J. (2015)
The success of an e-learning project depends largely on the quality of applications and tools used to support the learning process. Meanwhile, the quality of software depends largely on proper stakeholders? identification in the requirements stage during the development process. Although some studies exist which have identified key stakeholders in e-learning domain, most of them do not perform a deep analysis of the stakeholders and their contexts, necessary to consider educational and cultural issues in this type of environment. The aim of this paper is to present the application of a method for the identification and analysis of stakeholders, which is adapted to e-learning domain. This method was used in a case study considering university environments.